Editorial - Armstrong , Anona (Journal of Law and Governance, 2014)
This edition of the Journal is the first publication under our new publications management system. It presents an eclectic mix of papers ranging from papers with results dawn from analyses of survey data from small business, to strategic decisions about the factors affecting investment. It concludes with a more philosophical paper which addresses the ethical issues of cultural and moral behaviour in the Australian Defence Force.